Comparison of Dark Personality Traits, Self-Compassion, Mindfulness, and Ego Strength in Depressed and Obsessive-Compulsive Patients - Pakizeh, Zahra; Hojjati, Atefeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to compare dark personality traits, self-compassion, mindfulness, and ego strength in patients with depression and obsessive-compulsive disorder.Methods and Materials: The research design was a causal-comparative method. The statistical population of this study included all individuals with a confirmed psychiatric and clinical diagnosis of obsessive-compulsive disorder and major depressive disorder in the province of Qom. The sample consisted of 80 individuals with obsessive-compulsive disorder and depression, selected using purposive sampling. The instruments used in this study included the Beck Depression Inventory, the Revised Obsessive-Compulsive Questionnaire, the Dark Triad Personality Questionnaire, the Self-Compassion Scale, the Mindfulness Questionnaire, and the Psychological Ego Strength Questionnaire. To analyze the findings, univariate and multivariate analysis of variance tests were used, and data analysis was conducted using SPSS.22 software.Findings: The findings indicated that the mean score of dark personality traits in the obsessive-compulsive group was higher than in the depression group. Additionally, self-compassion, mindfulness, and ego strength were higher in the obsessive-compulsive group compared to the depression group (p < 0.01).Conclusion: The study reveals significant differences between individuals with obsessive-compulsive disorder and major depressive disorder in dark personality traits, self-compassion, mindfulness, and ego strength. These findings suggest that these psychological traits play a crucial role in the manifestation and severity of these disorders.